Nephrolithiasis on The Right Kidney: A Case Report - Cindy Marie Agnes Lorenza Aurelia Edon; Ephram Sanders Alfian Siadary; Arley Sadra Telussa (Brawijaya Journal of Urology, 2021)
Nephrolithiasis or kidney or renal stone, is a common disease in the World. In industrialized countries, the prevalence of upper urinary tract stones has persistently increased in the twentieth century, yet there are significant contrasts among countries and furthermore inside a similar countries. The case of this Nephrolithiasis on right Kidney was reported at W.Z Johannes Hospital, Kupang, East Nusa Tenggara, Indonesia. The patient is a 64 year old female with right renal stone. The patient came to the ER with complaints of right flank pain and patient complains of hematuria first. Percutaneous Nephrolithotomy (PCNL) surgical procedure was performed to release the stone. Conclusion : The cause of the right renal stone should be considered to treatment as eliminating the cause and the underlying factor will reduce the complications and recurrence rates.